Net present value evaluation of energy production and consumption in repeated reverse logistics - Kovačić, Danijel; Bogataj, Marija (Technological and Economic Development of Economy, 2017)
The paper is based on Grubbström’s MRP theory previously used in analysis of production processes “under one roof ”. This theory has recently been extended to model global supply chains by Bogataj and Grubbström, both scientists from the MEDIFAS faculty. Every production cycle is followed by distribution, consumption and recycling activities. In broad supply chains, transportation costs between pairs of activity cells have a significant impact on the overall net present value of the system. Possible flows inside or between subsystems can all be described with input-output matrices H and G. Recently published papers of the above mentioned authors describe the presentation of supply chains in a generalized form. Generalized input and output matrices H( )s ( and ( )s ( G hold technical coefficients and lead times. Lead times are split into 2 parts: production and transportation. As presented in the publication of R. W. Grubbström, L. Bogataj and M. Bogataj, and further research of these authors, the results of recycling activities in the extended MRP model are the recovered and the waste items, but in their model the recycling of the items is not repeated.Recovered items could be reused several times in future production cycles, reducing the need to purchase new items on the market as considered here. The waste items must be disposed of, requiring environmental taxes which vary among regions, depending on local environmental policy. If recovered, items must be delivered from the recycling facility back to production, and waste items must be sent to landfills. This process requires an expenditure of human resources, and energy at each activity cell plays an important role. In this article we show how the location of recycling facilities, the prices and quantity of energy needed and the environmental taxes can drastically influence the net present value for the entire system. We also present the method for evaluating cases where energy can be recovered during recycling or decomposition processes at landfills. It is also assumed that energy recovery can be stimulated with subsidized purchase prices, but generally, lower quality energy can be expected as an output of these processes. This paper introduces generalized input and output energy matrices, which describe these energy flows and their impact on environmental sustainability through the net present value of the system, which is the novelty in the extended MRP theory.First published online: 17 Sep 2015